Demanding choices : opinion, voting, and direct democracy - Bowler, Shaun, 1958- (Book collections on Project MUSE., 1998)
In Demanding Choices, Shaun Bowler and Todd Donovan explore how voters make decisions in direct referenda. The authors ask if voters have easy and accessible information about an issue and if the choices voters make seem sensible given their interests and the information they have. Looking at the way voters respond to different kinds of questions, the authors suggest that while direct democracy has its failings, the flaws do not necessarily lie with citizens being "duped", or with voters approving propositions they do not want or understand.